PENGARUH SOSIALISASI GENDER TERHADAP PEMBENTUKAN POLA PIKIR PEREMPUAN ACEH (Studi Kasus di Banda Aceh dan Aceh Besar) - Miskahuddin, Miskahuddin (Ar Raniry : International Journal of Islamic Studies, 2014)
Discourse on gender is not depleted as discussed and studied scientifically until now. Debate in academic circles about gender are already accustomed discussed and no longer be something foreign. Even today there are efforts to encourage all of the activities and programs should be concerned with aspects of gender equality. Development of previously unknown information about only the consumption of the current academic has penetrated up to the village level, and unknown to many people , both lay and the learned knowledge. This occurs because of the reality of gender socialization undertaken by various parties, including government agencies through the empowerment of women and children , as well as by non-governmental organizations ( local and international NGOs ) . Many people received information about the gender , clearly establish its own thinking paradigm for women in Aceh . To see about women thinking about gender Aceh after getting the socialization of NGOs , the research was conducted.Keywords : Influence , Socialization , Gender